STUDI KARAKTERISTIK DAN PENGGUNAAN OBAT PADA PENDERITA HEPATITIS B DI RUMAH SAKIT PEMERINTAH KOTA MANADO PERIODE JANUARI 2011 – DESEMBER 2012 - Luntungan, Lady zha-zha; Fatimawali, Fatimawali; Bodhi, Widdhi (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACTHepatitis B is a disease caused by the virus called hepatitis B wich characterized by aninflammation that occurs in organs such as the liver. The transmission of Hepatitis B is higherthan the transmission of the HIV virus. This study aimed to investigate the characteristics anduse of the drug in hepatitis B patients in the Government Hospital in Manado. This researchis a descriptive study based on retrospective data collection for 2 years survey from January2011 to December 2012. The respondent of this research involve of 70 patients with HepatitisB medical record. The results showed that based on group age, responden with age group 46-65 has the highest percentage by 31 patients (44.3%), based on gender, males have thehighest percentage of total of 47 patients (67.1%), based on the duration of treatment, thehighest percentage is shown by the patient with 1 day threatment as 21 patients (30%). Basedon therapeutic treatment this research divided it into 2 kind of threatment. The first us singleagent therapy Hepamax consist of 27 patients (38.6%) The second therapy is combinationbetween Hepamax and Curcuma wich consist of 9 patients (12.9%). This research conductedbased on 100% oral route of medicine threatment.Keywords: Hepatitis B, Hepatitis B medicine, Singel Therapy, Combination Therapy